Complete mitochondrial genome sequence analysis revealed double matrilineal components in Indian Ghoongroo pigs - Pranab Jyoti Das; Satish Kumar; Manasee Choudhury; Seema Rani Pegu; K. Meera; Rajib Deb; Sunil Kumar; Santanu Banik; Vivek Kumar Gupta (Scientific Reports)
Abstract This research aimed to characterize the mitochondrial genome of the Ghoongroo (GH) pig, a notable breed in India, along with its crossbred varieties, to elucidate their matrilineal components, evolutionary history, and implications for conservation. Seven pigs (5 GH, 2 crossbred, namely Rani and Asha) were sequenced for complete mitochondrial genome, while 24 pigs (11 GH, 6 Rani, and 7 Asha) were sequenced for the complete D-loop of the mitochondrial genome. The genome size of these pigs was determined to be 16,690 bp. Analysis of the mitochondrial sequences and phylogenetics uncovered two distinct matrilineal components within the GH population, a phenomenon also observed in its crossbred counterparts, Rani and Asha. Phylogenetic analysis demonstrated a clear clustering of GH sequences into two clades, indicating the presence of two independent maternal lineages. The phylogenetic study using complete mitogenome also indicated that GH pigs were originated locally from Indian wild boar independently from Asian and European pig population. Haplotype analysis from complete D-loop sequences revealed 10 different haplotypes, with some sequences shared among GH, Rani, and Asha, while others differed due to varying matrilineal origins. The haplotype analysis using complete mitogenome sequences revealed 16 different haplotypes with some shared sequences among GH. Furthermore, examination of tRNA genes and nucleotide composition of different genes namely rRNAs, COX1, COX2, ATP6, ND4, ND5, ND6, Cytb offered insights into genetic diversity within these pigs. The findings suggest that geographical isolation and historical events likely contributed to the emergence of distinct maternal lineages within the GH breed. This study underscores the significance of mitochondrial DNA analysis in uncovering hidden genetic diversity within seemingly uniform populations. The molecular insights gained into the genetic makeup of GH pigs could aid in designing effective breeding programs for conservation efforts and highlight its significance in understanding the broader context of pig domestication in India.